I have recently started to learn about Fourier series, which have been defined by the complex exponential. So a Fourier series is on the form: $$\sum_{n=-\infty}^{\infty} c_ne^{inx}$$

Where the Fourier coefficient $c_n$ is defined as: $$ c_n = \frac{1}{2\pi} \int_{-\pi}^{\pi}f(y)e^{-iny}dy$$

If I am suppose to find the Fourier series of the sum:

$$ \sum_{n=0}^{\infty}\frac {\cos(nx)}{n!} $$

how am I suppose to do it with this definition? Hope somebody can give a hint or explain a method to find the Fourier series.


Remember that $e^{it} = \cos(t)+i\sin(t)$.

We have, for $n\in\mathbb{Z}\setminus\{0\}$, \begin{equation*} \begin{split} 2\pi c_n & =\int_{-\pi}^{\pi} \sum_{k=0}^{\infty} \frac{\cos(ky)}{k!}e^{-iny}\, {\rm d}y \\ & = \sum_{k=0}^{\infty} \frac{1}{k!} \int_{-\pi}^{\pi} \cos(ky)e^{-iny} \, {\rm d}y \\ \end{split} \end{equation*}

But \begin{equation*} \begin{split} \int_{-\pi}^{\pi} \cos(ky)e^{-iny} \, {\rm d}y & = \int_{-\pi}^{\pi} \cos(ky)(\cos(-ny)+i\sin(-ny)) \, {\rm d}y \\ & = \int_{-\pi}^{\pi} \cos(ky)\cos(-ny) \, {\rm d}y + i\overbrace{\int_{-\pi}^{\pi} \cos(ky)\sin(-ny)\, {\rm d}y}^0 \\ & = \int_{-\pi}^{\pi} \cos(ky)\cos(-ny)\,{\rm d}y, \\ \end{split} \end{equation*} which is zero, if $k\ne|n|$, and $\pi$, otherwise.

Thus, $2\pi c_n = \frac{\pi}{|n|!}$ and therefore $c_n = \frac{1}{2(|n|!)}.$ (for $n\ne0$)

Edit: For the $c_0$ term, we have \begin{equation*} \begin{split} 2\pi c_0 & = \sum_{k=0}^{\infty}\frac{1}{k!} \int_{-\pi}^{\pi} \cos(ky) \, {\rm d}y \end{split} \end{equation*} and $\int_{-\pi}^{\pi} \cos(ky)\, {\rm d}y$ equals $2\pi$, if $k=0$, and $0$, otherwise. So $c_0 = 1$.

We conclude that the Fourier serie of $\sum_{k=0}^{\infty}\frac{\cos(ky)}{k!}$ is $$\frac12+\sum_{n=-\infty}^{\infty} \frac{e^{inx}}{2(|n|!)}.$$

Notice that $\frac{e^{i\cdot0\cdot x}}{2(0!)} = \frac12$. Then \begin{equation*} \begin{split} \sum_{n=-\infty}^{\infty} c_n e^{inx} & = c_0+\sum_{n\ne0} c_n e^{inx} \\ & = 1+\sum_{n\ne0}\frac{e^{inx}}{2(|n|!)} \\ & = \frac12 + \frac{e^{i\cdot0\cdot x}}{2(0!)}+ \sum_{n\ne0}\frac{e^{inx}}{2(|n|!)} \\ & = \frac12 + \sum_{n=-\infty}^{\infty}\frac{e^{inx}}{2(|n|!)}. \end{split} \end{equation*}

| cite | improve this answer | |
  • $\begingroup$ So the Fourier series of this sum would be: $\frac {1}{2(|n|!} \cdot e^{inx}$ but what about the $c_0$ term, shouldn't that be included as well? $\endgroup$ – Mads Jeppesen May 7 '18 at 7:34
  • $\begingroup$ @MadsJeppesen I've edited my answer, hope it helps. $\endgroup$ – Rodrigo Dias May 7 '18 at 9:14
  • $\begingroup$ It helps a lot, thank you! Just a minor question: if $c_0 = 1$ how do you get $\frac {1}{2}$ and is it possible to perform the same computation, but instead of having $2\pi c_n = ... $ just do it with $c_n = \frac {1}{2\pi} ... $ $\endgroup$ – Mads Jeppesen May 7 '18 at 11:11
  • $\begingroup$ @MadsJeppesen It's just a nice/tricky way to write it. See my last edit. $\endgroup$ – Rodrigo Dias May 7 '18 at 11:39
  • $\begingroup$ Sorry, I have one last question: when you evaluate $\int_{-\pi}^{\pi}cos(ky)$ and say that is is equal to $2\pi$ if $k=0$ how is that true? Because when I take the integral of $cos(ky)$ i get $\frac{sin(ky)}{k}$ which is undefined when $k=0$ $\endgroup$ – Mads Jeppesen May 7 '18 at 16:48

Observe by definition, we have \begin{align} \cos(n x) = \frac{e^{inx}+e^{-inx}}{2} \end{align} then it follows \begin{align} \sum^\infty_{n=0}\frac{\cos(nx)}{n!} = \frac{1}{2}+\sum^\infty_{k=-\infty} \frac{e^{ikx}}{2(|k|!)}. \end{align}

| cite | improve this answer | |
  • $\begingroup$ When you have that $$ \sum^\infty_{n=0}\frac{\cos(nx)}{n!} = \frac{1}{2}+\sum^\infty_{k=-\infty} \frac{e^{ikx}}{2(|k|!)} $$ To you simply use that $cos(nx) = \frac {e^{inx}+e^{-inx}}{2}$, and if this is the case, then how do you get $\frac {1}{2}$ outside of the sum? $\endgroup$ – Mads Jeppesen May 7 '18 at 7:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.